Persistent poor glycaemic control in individuals with type 2 diabetes in developing countries: 12 years of real-world evidence of the International Diabetes Management Practices Study (IDMPS) - Aschner, Pablo (2020)
We evaluated the secular trend of glycaemic control in individuals with type 2 diabetes in developing countries, where data are limited. Erratum in Correction to: Persistent poor glycaemic control in individuals with type 2 diabetes in developing countries: 12 years of real-world evidence of the International Diabetes Management Practices Study (IDMPS). Aschner P, Gagliardino JJ, Ilkova H, Lavalle F, Ramachandran A, Mbanya JC, Shestakova M, Chantelot JM, Chan JCN. Diabetologia. 2020 May;63(5):1088-1089. doi: 10.1007/s00125-020-05118-3.